Daily field checking list by Walter Rosene, March 28, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, March 28, 1936. Also notes he observed twenty-four geese at McCaskey pond in Boone County. Plustek--flatbed